Gamma Rays and Sodium Azide Induced Genetic Variability in High-Yielding and Biofortified Mutant Lines in Cowpea [Vigna unguiculata (L.) Walp.] - Raina, Aamir; Laskar, Rafiul Amin; Wani, Mohammad Rafiq; Jan, Basit Latief; Ali, Sajad; Khan, Samiullah (Frontiers in Plant Science, 2022)
With the twin pressures of high population growth and extreme weather events, developing countries are the worst hit in meeting the food demands of their people, with millions unable to access adequate and nutritionally balanced food. Crop production must be increased by 70% to keep up with the food demands of an rapidly growing population which is expected to rise to 9.6 billion by 2050. Legumes are ideal food crops to increase agricultural productivity and sustainable agriculture development goals. Cowpea, a warm-season grain legume, is often categorized as a neglected crop with immense scope of genetic improvement through proper breeding strategies. A multi-year field experiment of induced mutagenesis was conducted with the objectives of increasing seed yield and genetic variability in the agro-economic traits of two cowpea varieties treated with different doses of gamma (γ) rays and sodium azide (SA). The study was also aimed to optimize different doses of γ rays and SA employed individually and in combinations. Quantitative trait analysis revealed a maximum increase in seed yield from M2 to M3 generation. Among the ten quantitative traits studied, seeds per pod and seed weight positively correlated with a major direct impact on yield. An extensive phenotypic selection cycle from M2-M4 generations resulted in isolating new high yielding and nutrient-dense mutant lines. Such high yielding biofortified mutant lines with enhanced genetic variability could serve as a donor of elite genes and represent a valuable genetic resource for improving low-yielding warm-season grain legumes